The socioeconomic and environmental impacts of wood energy value chains in Sub-Saharan Africa: a systematic map protocol - Cerutti, P.O.; Sola, P.; Chenevoy, A.; Iiyama, Miyuki; Yila, Jummai Othniel; Zhou, W.; Djoudi, H.; Eba'a Atyi, R.; Gautier, D.; Gumbo, D.J.; Kuehl, Y.; Levang, P.; et al. (Springer, 2015)
The vast majority of households in Sub-Saharan Africa (SSA) depend on wood energy—comprising firewood and charcoal—for their daily energetic needs. Such consumption trends are expected to remain a common feature of SSA’s wood energy production and supply chains, at least in the short- to medium-terms. Notwithstanding its importance, wood energy generally has low priority in SSA national policies. However, the use of wood energy is often considered a key driver of unsustainable management and negative environmental consequences in the humid and dry forests.To date, unsystematic assessments of the socio-economic and environmental consequences of wood energy use have underplayed its significance, thus further hampering policy debates. Therefore, a more balanced approach which considers both demand and supply dynamics is needed. This systematic map aims at providing a comprehensive approach to understanding the role and impacts of wood energy across all regions and aspects in SSA.The objective of this systematic map is to collate evidence from studies of environmental and socio-economic impacts of wood energy value chains, by considering both demand and supply within SSA. The map questions are framed using a Populations, Exposure, Comparators and Outcomes (PECO) approach. We name the supply and demand of wood energy as the “exposure,” composed of wood energy production, harvesting, processing, and consumption. The populations of interest include both the actors involved in these activities and the forest sites where these activities occur. The comparator is defined as those cases where the same wood energy activities occur with i) available/accessible alternative energy sources, ii) regulatory frameworks that govern the sector and iii) alternative technologies for efficient use. The outcomes of interest encompass both socioeconomic and environmental impacts that can affect more than the populations named above. For instance, in addition to the direct socioeconomic impacts felt by participants in the wood energy value chain, forest dwellers may experience livelihood changes due to forest degradation caused by external harvesters. Moreover, intensified deforestation in one area may concurrently lead to forest regeneration in another.